Performance evaluation of holonic-based online scheduling for a switch arrival system. Issue 3 (2015) - Indriago, Carlos; Cardin, Olivier; Bellenguez-Morineau, Odile; Rakoto, Naly; Castagna, Pierre
Abstract: Hybrid system class, which includes systems with piecewise continuous evolution and whose changes are related to the evolution of discrete variables are classically structured in three different levels, the controller, the system and the interface. This kind of system is usually modeled through commutation models representing the whole system. Any reconfiguration process is therefore highly complex, as the calculation times are strongly linked to the size of the system. An adaptation of a holonic reference architecture on a hybrid system is proposed, this proposed model is composed of the union of the hybrid model and the holonic model, where the controller is represented by the product holon and the order holon, the interface is represented by the logical part of the resource holon, and finally the system is represented by the physical part of the resource holon. The aim of this paper is to evaluate the performance of a simple predictive-reactive control using a holonic approach applied to a switch arrival system. Four configurations of study case are studied in simulation in order to evaluate the number of switches, whose optimal value is obtained thanks to a MILP model.